2015
DOI: 10.1007/s00262-014-1650-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint combinations from mouse to man

Abstract: The discovery that antibody blockade of the T cell co-inhibitory receptor cytotoxic T lymphocyte-associated protein 4 (CTLA-4) can restore tumor immunity against many murine transplantable tumors leading to complete rejection of established cancer forever changed the field of immunotherapy. In more robust murine models as well as human cancer, however, CTLA-4 blockade alone can slow tumor growth and extend patient survival, but is rarely curative. Subsequent studies have revealed a large family of T cell immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…S1). Results from these experiments demonstrated limited benefit from CTLA-4 monotherapy, in keeping with prior reports (4, 5); however, treatment with the CTLA-4 antibody together with PARP inhibition resulted in a synergistic therapeutic effect with long-term tumor-free survival in a majority of animals (Fig. 4A).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…S1). Results from these experiments demonstrated limited benefit from CTLA-4 monotherapy, in keeping with prior reports (4, 5); however, treatment with the CTLA-4 antibody together with PARP inhibition resulted in a synergistic therapeutic effect with long-term tumor-free survival in a majority of animals (Fig. 4A).…”
Section: Resultssupporting
confidence: 89%
“…Ovarian cancer has been identified as a rational target for immune therapy; however, these tumors have been considered relatively resistant to checkpoint blockade (3, 4). This is based on studies in murine models and clinical trials that showed limited response of ovarian tumors to CTLA-4 antibodies (5–7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to increase the response rate to checkpoint blockade, several combination therapies have been developed (Ai and Curran, 2015). Among them, the combination with anti-PD-1 and anti-Cytotoxic T Lymphocyte-associated Antigen-4 (CTLA-4) has shown the best improvement in clinical trials (Hammers et al, 2014; Postow et al, 2015; Wolchok et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the work of at least two decades and the unravelling of complex regulatory pathways involved in the immune responses to cancer. Specifically, there has been a great deal of progress in our understanding of how T cell activation is controlled through "immune checkpoints" for the generation of adaptive immune responses to malignancy, and of inhibiting these interactions to achieve significant and clinically meaningful antitumour effects [1,2]. Currently (July 2015), the largest group of immunotherapy trials of the total of >250 registered at clinicaltrials.…”
mentioning
confidence: 99%